The impact of the strengths and weaknesses in Iraqi newspapers: The evolution of the consumer - the reader (Journal of Accounting and Financial Studies ( JAFS ), 2013)
The first section of this research discussed  the manner of the research from many sides like the problem it faces, importance of it , its targets ,boundaries, the way to collect and get information's and its assumption.When the second chapter discussed the press – manufacturing and the development ,importance and types of newspapers, also its merits and weaknesses.The third chapter talked about the scientific side and how to choose an assumption for the research . as it talked also about the apparent honest and stability tests that help in analyzing the research until getting results and so the right assumption for  the research will be chosen.And finally, the fourth chapter put highlight on the best research conclusions and the recommendation of the merits and weakness in the Iraqi newspapers from the sight (opinion) of the consumer (the reader).